Ideal profile for public managers of the municipality of Cota Cundinamarca (2014)
While occupational profiles for office in some parts of our national geography have been established so that they are played by people with the right for the job skills, it is also true that in some places still, these profiles have been maintained in time with minimum education and experience, it is also the case for other territorial entities have grown or changed rapidly in recent years due to less predictable external circumstances, which demand a new breed of managers for these locations, one professional different capabilities and exceptional skills and untraditional that are suitable for office and meet the expectations and meet the needs of their community to exercise effectively and efficiently managing the resources at their disposal.